Icariin Attenuates Amyloid-β (Aβ)-Induced Neuronal Insulin Resistance Through PTEN Downregulation - Zou, Xiaomei; Feng, Xiyao; Fu, Yalin; Zheng, Yuyang; Ma, Mingke; Wang, Changhua; Zhang, Yemin (Frontiers in Pharmacology, 2020)
Neuronal insulin resistance is implicated in neurodegenerative diseases. Icariin has been reported to improve insulin resistance in skeletal muscle cells and to restore impaired hypothalamic insulin signaling in the rats with chronic unpredictable mild stress. In addition, icariin can exert the neuroprotective effects in the mouse models of neurodegenerative diseases. However, the molecular mechanisms by which icariin affects neuronal insulin resistance are poorly understood. In the present study, amyloid-β (Aβ) was used to induce insulin resistance in human neuroblastoma SK-N-MC cells. Insulin sensitivity was evaluated by measuring insulin-stimulated Akt T308 phosphorylation and glucose uptake. We found that the phosphatase and tensin homologue deleted on chromosome 10 (PTEN) mediated Aβ-induced insulin resistance. Icariin treatment markedly reduced Aβ-enhanced PTEN protein levels, leading to an improvement in Aβ-induced insulin resistance. Accordingly, PTEN overexpression obviously abolished the protective effects of icariin on Aβ-induced insulin resistance. Furthermore, icariin activated proteasome activity. The proteasome inhibitor MG132 attenuated the effects of icariin on PTEN protein levels. Taken together, these results suggest that icariin protects SK-N-MC cells against Aβ-induced insulin resistance by activating the proteasome-dependent degradation of PTEN. These findings provide an experimental background for the identification of novel molecular targets of icariin, which may help in the development of alternative therapeutic approaches for neurodegenerative diseases.